Successful Treatment with Expanded Mesenchymal Stem Cell Therapy for Muscle Wasting Post-Surgical Repair of Achilles Tendon - Hassan Mubark (Issues and Developments in Medicine and Medical Research Vol. 3, 2022)
This study investigates the efficacy of local implantation of biological therapy to repair injured calf muscles and tendons. The Achilles tendon (AT) is one of the most frequently ruptured lower leg tendons. AT rupture occurs when sudden forces apply upon the Achilles tendon during vigorous physical activities that involve abrupt swivelling on a foot or a fast burst of speed. Chronic AT rupture generally occurs 4-6 weeks after injury; symptoms include pain, ankle stiffness, and reduced strength. There is no typical treatment, mainly when a significant gap between the tendon ends; it warrants reconstruction, commonly with flexor hallucis longus tendon (FHLT) transfer for all defects over 2cm. This case study features a 44-year-old female patient who suffered a left AT rupture during a netball game. Initially, she had conservative treatment, but it spontaneously ruptured again, necessitating reconstruction surgery with FHLT transfer. She developed calf muscle weakness and atrophy at the grafted musculo-Achilles junction. Her symptoms included the inability to perform a single heel raise, decreased recreational activities, and calf muscle wasting and weakness. The Foot & Ankle Disability Index (FADI) score was 74. Her orthopaedic surgeon declined any further surgical intervention, given it will not offer any benefit to the patient. She has opted for a trial of autologous adipose-derived expanded mesenchymal stem cell therapy (MSCs) combined with platelet-rich plasma (PRP). Six months following the treatment, she had a good outcome evidenced by improved daily activities, heel-raise, and running slowly for the first time after several years post reconstruction surgery. Her FADI score rose to 91.3, and a six-month post-treatment MRI revealed an increased signal at the musculo-Achilles junction suggesting a healing process. This case presents a successful outcome with a single MSCs and PRP, indicating we can try MSC therapy to repair wasted calf muscle and tendon from previous scars.